Baricitinib in rheumatoid arthritis: evidence-to-date and clinical potential. (February 2017) - Kuriya, Bindee; Cohen, Marc D.; Keystone, Ed
Biologics have changed expectation and outcomes for rheumatoid arthritis (RA). However, the optimal duration and sequence of therapy for this disease has yet to be determined. Also, a significant number of patients do not satisfactorily respond to currently available therapies. The Janus kinase (JAK) inhibitors represent a new class of therapies for RA. These drugs work uniquely by inhibiting intracellular pathways thought to be important in the pathogenesis of RA. They are available as oral agents, which is also different from the currently available biologics. Baricitinib has now been evaluated in four phase III clinical trials, and although safety concerns cannot fully be answered until the drug is studied over longer periods of time, the data to date suggest that this drug with its once daily dosing, rapid onset of action and efficacy as monotherapy represents an important addition to the RA therapeutic armamentarium. Further study and experience will better define how baricitinib will be used and by which patients.